Biological and biochemical indicators in derelict soils subject to erosion - Garcia, C.; Hernandez, T. (Soil Biology and Biochemistry, 1997)
n 21 derelict soils from a semi-arid Spanish Mediterranean area, with a lithological sub- strate of Ioams, submitted to a high degree of erosion, several biological and biochemical properties in- dicative of the soil degradation leve1 were determined. The organic matter content of these soils was very low (mean value = 11.8 g kg-‘), approximately one-third of the average value for organic matter content of natura1 soils in the same zone. Biological properties such as basal respiration and biomass C also had low values and were positively correlated with the organic matter content. Low values for de- hydrogenajse and catalase activity were indicative of low biological activity of the degraded soils. A positive correlation was found between the hydrolases related with the N, P, C and S cycles (urease, proteases, fl-glucosidase and arylsulphatase), as wel1 as between these hydrolases and the organic matter content. Principal component analysis showed that ah the variables studied, except catalase and qCOr, had a similar behaviour. There was a negative correlation between many of the properties studied and electrical conductivity, which agreed with the higher degree of biological and biochemical degradation found in gypsiferous soils with a higher salt content. Arylsulphatase and p-glucosidase activity were the hydrolases most affected by soil erosion processes
Keywords: biochemical parameters (PG); Biological indicators; derelict soils; Soil degradation